FAKTOR YANG BERHUBUNGAN DENGAN KEAKTIFAN KUNJUNGAN IBU BALITA USIA 24-60 BULAN KE POSYANDU DI DESA SIALAGUNDI KECAMATAN SIPIROK KABUPATEN TAPANULI SELATAN TAHUN 2020 - harahap, siti aisyah (Jurnal Inovasi Kesehatan Masyarakat, 2021)
Based on the preliminary survey conducted, it is known that the number of mothers visiting children under five to Posyandu in Desa Sialagundi , Kecamatan Sipirok , Kabupaten South Tapanuli in 2019 did not reach the national target of Posyandu visits of 90%. This study aims to analyze the relationship between your mother's knowledge, mother's attitude, health care provider support, family support and the distance of the posyandu to your visit to Posyandu. This type of research is quantitative with a cross-sectional approach conducted from March 2020 in Desa Sialagundi, Kecamatan Sipirok, Kabupaten South Tapanuli in 2020. This study was conducted on 60 mothers. Statistical analysis shows that all independent variables are related to the activity of your mother's visit to Posyandu with p-values (Mother's Knowledge: 0.002, Mother's Attitude: 0.001, Support of Health Officers: 0, 004, Family Support: 0.002, Posyandu Distance: 0.015). At the Multivariate analysis stage it is known that the most related variable is the Attitude of the Mother with sig. 0.041 and Family Support has the largest Exp (B) value: 8.264) so it can be assumed that mothers who get family support will be 8.264 times more active in visiting Posyandu. It is hoped that Health Officers will be more active in providing information about the importance of routine Posyandu visits, especially to mothers and families.